2020
DOI: 10.3390/ijms21207443
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Therapeutic Agents Targeted towards Mitigating the Events Associated with Amyloid-β Cascade in Alzheimer’s Disease

Abstract: One of the most commonly occurring neurodegenerative disorders, Alzheimer’s disease (AD), encompasses the loss of cognitive and memory potential, impaired learning, dementia and behavioral defects, and has been prevalent since the 1900s. The accelerating occurrence of AD is expected to reach 65.7 million by 2030. The disease results in neural atrophy and disrupted inter-neuronal connections. Amongst multiple AD pathogenesis hypotheses, the amyloid beta (Aβ) cascade is the most relevant and accepted form of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 138 publications
(315 reference statements)
1
31
0
Order By: Relevance
“…Keywords TDP-43 • Tau • Amyloid-β (Aβ) • Alzheimer's disease • Limbic-predominant age-related TDP-43 encephalopathy (LATE) • Frontotemporal lobar degeneration (FTLD) Perspectives Pathophysiological spectrum in Alzheimer's disease Alzheimer's disease (AD), a devastating, fatal neurodegenerative disease of aging, features the presence of extracellular amyloid-β (Aβ) plaques and intracellular tangles of hyperphosphorylated tau in the brain [1].For decades, prevention or clearance of Aβ plaques have been the major therapeutic goals in the pursuit of a treatment for AD. This was a rational approach given that mutations in genes involved in amyloid processes cause some inherited (familial) cases of AD [2]. Unfortunately, most clinical trials have failed thus far to demonstrate a significant benefit to patients, raising the need to pursue additional strategies [3].…”
mentioning
confidence: 99%
“…Keywords TDP-43 • Tau • Amyloid-β (Aβ) • Alzheimer's disease • Limbic-predominant age-related TDP-43 encephalopathy (LATE) • Frontotemporal lobar degeneration (FTLD) Perspectives Pathophysiological spectrum in Alzheimer's disease Alzheimer's disease (AD), a devastating, fatal neurodegenerative disease of aging, features the presence of extracellular amyloid-β (Aβ) plaques and intracellular tangles of hyperphosphorylated tau in the brain [1].For decades, prevention or clearance of Aβ plaques have been the major therapeutic goals in the pursuit of a treatment for AD. This was a rational approach given that mutations in genes involved in amyloid processes cause some inherited (familial) cases of AD [2]. Unfortunately, most clinical trials have failed thus far to demonstrate a significant benefit to patients, raising the need to pursue additional strategies [3].…”
mentioning
confidence: 99%
“…van der Stelt et al 37 has shown that twelve days after the injection of β‐amyloid into the frontal cortex result in neuronal impairment in the hippocampus (CA1, CA2 and CA3 areas). Moreover, the Aβ cascade hypothesis is the most relevant and accepted theory related to AD pathophysiology, which are formed by the misfolding of Aβ monomers 39 . Therefore, on the basis of these studies, a rat model of the AD was used by bilateral injection of β‐amyloid into the frontal cortex and effects of crocin were investigated in the CA1 region.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Aβ cascade hypothesis is the most relevant and accepted theory related to AD pathophysiology, which are formed by the misfolding of Aβ monomers. 39 Therefore, on the basis of these…”
Section: Discussionmentioning
confidence: 99%
“…Thought to start 20 years or more before, the symptoms arise with brain alterations that remain unnoticeable to the affected person. Individuals after years of brain alterations experience noticeable symptoms (i.e., language problems and memory loss) [ 26 , 27 , 28 , 29 ]. The occurrence of symptoms is due to damage or destruction of nerve cells (neurons) in brain regions involved in learning, thinking, and memory [ 26 , 30 , 31 ].…”
Section: Brief Overview Of Neurodegenerative Diseases (Nds)mentioning
confidence: 99%